2015
DOI: 10.1242/dev.125724
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contraction activates endocardial Notch signaling to modulate chamber maturation in zebrafish

Abstract: Congenital heart disease often features structural abnormalities that emerge during development. Accumulating evidence indicates a crucial role for cardiac contraction and the resulting fluid forces in shaping the heart, yet the molecular basis of this function is largely unknown. Using the zebrafish as a model of early heart development, we investigated the role of cardiac contraction in chamber maturation, focusing on the formation of muscular protrusions called trabeculae. By genetic and pharmacological abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 90 publications
(116 reference statements)
14
141
0
Order By: Relevance
“…Similarly, Notch signaling could not be detected in endocardial cells in tnnt2a morphants at 75 hpf. These observations are in line with previous reports showing that notch1b expression is undetectable in tnnt2a morphants at 48-50 hpf (Samsa et al, 2015) and is also downregulated in gata2 morphants, which have a lower blood viscosity (Vermot et al, 2009). Taken together, these results indicate that both Notch and Wnt/β-catenin signaling depend on cardiac contraction and/or blood flow.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Notch signaling could not be detected in endocardial cells in tnnt2a morphants at 75 hpf. These observations are in line with previous reports showing that notch1b expression is undetectable in tnnt2a morphants at 48-50 hpf (Samsa et al, 2015) and is also downregulated in gata2 morphants, which have a lower blood viscosity (Vermot et al, 2009). Taken together, these results indicate that both Notch and Wnt/β-catenin signaling depend on cardiac contraction and/or blood flow.…”
Section: Discussionsupporting
confidence: 93%
“…After these injections, the signal of the Notch reporter was no longer detectable in endocardial cells at 75 hpf (n=7 larvae) (Fig. 5F,G) in agreement with a recent report (Samsa et al, 2015). Similarly, the strong signal of the Wnt/β-catenin signaling reporter in AVC endocardial cells was downregulated in tnnt2a morphants (n=8 larvae) (Fig.…”
Section: The Immature Valve Comprises Two Different Sets Of Cellssupporting
confidence: 91%
“…Previous studies have shown that Erbb2 signaling is essential for trabeculation (3,6,7,10,11). Moreover, disturbing blood flow or cardiac contractility in the ventricle perturbs trabeculation (4,12,13), suggesting an important role for mechanical forces in this process. Our understanding of the cellular mechanisms regulating trabeculation remains fairly limited.…”
Section: Cdh2-egfpmentioning
confidence: 99%
“…Some evidence suggests that Notch signalling may play a role in mechanosensitive pathways (Jahnsen et al, 2015). During zebrafish trabeculation, cilia play a role in sensing fluid forces and in inducing notch1b expression within the ventricular endocardium which, in turn, is required for correct trabeculation (Samsa et al, 2015). Studies in different model systems show that Notch expression defines regions within the embryonic endocardium that correspond with valve and chamber formation, and with ventricular trabeculation (De Luxán et al, 2015).…”
Section: Ecm Signalling In Mechanotransduction During Cardiac Cushionmentioning
confidence: 99%
“…Since endocardial Neuregulin is known to instruct myocardial cells to form trabeculae, it is possible that myocardial cells stochastically extend protrusions into the lumen, where they receive cues that determine their fates (Staudt et al, 2014). Shear forces sensed by the endocardium, as well as myocardial stretch forces, are also likely to affect pattern formation during trabeculation (Peshkovsky et al, 2011;Samsa et al, 2015). Thus, although the precise molecular and cellular mechanisms underlying trabeculation remain unclear, this process provides an excellent model for exploring the mechanisms underlying the interactions between endocardial and myocardial cells.…”
Section: Ecm Signalling In Mechanotransduction During Cardiac Cushionmentioning
confidence: 99%